MINI REVIEW: FOTOKATALISIS NANOPARTIKEL CaO TERHADAP ZAT WARNA ORGANIK SINTETIK - Salsabila, Aidilia Putri; Hiyahara, Irfan Ashari; Syaima, Husna (PROSIDING SEMINAR KIMIA, 2024)
Nanoparticles of CaO (CaO-NP) are currently a frequently used material in research due to their excellent catalytic and antibacterial activities, low toxicity, abundant availability, and relatively affordable manufacturing cost. One of their applications is as a photocatalyst, commonly employed to degrade organic materials such as dyes. This review discusses the utilization of CaO nanoparticles as photocatalysts for both cationic and anionic organic dyes. Literature results indicate that CaO-NP can serve as a catalyst in the photocatalysis of dyes, whether they are cationic or anionic. The percentage of degradation achieved varies, ranging from as low as 60% to as high as 99.21%. These varying results are attributed to the different parameters used in the diverse photocatalysis processes. Keywords: CaO Nanoparticle, Organic Dye, Photocatalysis